Factors that motivate high school agriculture teachers to teach - Ismail, Normala; Miller, Greg (American Association of Teacher Educators in Agriculture, 2021)
The purpose of this research was to describe the factors that motivate high school agriculture teachers to teach. The motivation to teach included intrinsic motivations, extrinsic motivations, and altruistic motivations. This was a census study using an online questionnaire that was sent to all (N = 252) high school agriculture teachers in Iowa. The Tailored Design Method with five contacts was used for data collection. The overall response rate was 47% (n = 119). Motivational factors were measured using a four-point Likert-type scale with the following response options: 1 = strongly disagree, 2 = disagree, 3 = agree, and 4 = strongly agree. Confirmatory factor analysis and maximum likelihood factor analysis were used to identify factors underlying individuals’ motivation to teach. Means and standard deviations were 3.24 (0.13) for intrinsic factors and 2.55 (0.19) for extrinsic factors, respectively, indicating these factors influenced individuals’ motivations to teach. In this study, altruistic factors retained through factor analysis aligned with the intrinsic factors. The findings were consistent with previous studies on intrinsic and extrinsic motivations based on self-determination theory. Even though teachers were drawn to the profession more strongly by intrinsic factors, both intrinsic and extrinsic factors are important in motivating agriculture teachers to teach. The study has implications for the design of induction and mentoring programs and for the administrative support of teachers.